Achieving sustainable quality in maternity services - using audit of incontinence and dyspareunia to identify shortfalls in meeting standards - Newburn Mary; Kettle Chris; Gyte Gill; Bick Debra; Newton Cindy; Clarkson James; Radford Jane; Johanson Richard (BMC, 2001)
Abstract Background Some complications of childbirth (for example, faecal incontinence) are a source of social embarrassment for women, and are often under reported. Therefore, it was felt important to determine levels of complications (against established standards) and to consider obstetric measures aimed at reducing them. Methods Clinical information was collected on 1036 primiparous women delivering at North and South Staffordshire Acute and Community Trusts over a 5-month period in 1997. A questionnaire was sent to 970 women which included self-assessment of levels of incontinence and dyspareunia prior to pregnancy, at 6 weeks post delivery and 9 to 14 months post delivery. Results The response rate was 48%(470/970). Relatively high levels of obstetric interventions were found. In addition, the rates of instrumental deliveries differed between the two hospitals. The highest rates of postnatal symptoms had occurred at 6 weeks, but for many women problems were still present at the time of the survey. At 9-14 months high rates of dyspareunia (29%(102/347)) and urinary incontinence (35%(133/382)) were reported. Seventeen women (4%) complained of faecal incontinence at this time. Similar rates of urinary incontinence and dyspareunia were seen regardless of mode of delivery. Conclusion Further work should be undertaken to reduce the obstetric interventions, especially instrumental deliveries. Improvements in a number of areas of care should be undertaken, including improved patient information, improved professional communication and improved professional recognition and management of third degree tears. It is likely that these measures would lead to a reduction in incontinence and dyspareunia after childbirth.